2013
DOI: 10.18388/abp.2013_1992
|View full text |Cite
|
Sign up to set email alerts
|

NOD1 and NOD2 receptors: integral members of the innate and adaptive immunity system.

Abstract: NOD-like proteins (NLR) are a specialized group of intracellular receptors, which constitute an essential component of the host innate immune system. They were discovered more than a decade ago, but research on this particular class of microbial detectors is still ongoing to allow for a better understanding of the mechanisms, recognition of microorganisms, transmission of signals, and carrying out the activation of inflammatory signaling pathways. In this review, we discuss the construction of NOD1 and NOD2 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 117 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…The present study identified CYLD as a novel and important inhibitor of RIPK2-dependent protective immune responses in Lm-infected murine macrophages. Activation of RIPK2 by the Lm-sensing intracellular pattern-recognition receptor NOD2 is essential for the downstream stimulation of the NF-κB and MAPK pathways ( 42 , 43 ), NOD2-induced immune responses in macrophages ( 25 ) and the control of listeriosis in vivo ( 17 ). Previous studies have shown that CYLD limited RIPK2-mediated activation of NF-κB by removing K63-polyubiquitin chains from NEMO ( 8 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study identified CYLD as a novel and important inhibitor of RIPK2-dependent protective immune responses in Lm-infected murine macrophages. Activation of RIPK2 by the Lm-sensing intracellular pattern-recognition receptor NOD2 is essential for the downstream stimulation of the NF-κB and MAPK pathways ( 42 , 43 ), NOD2-induced immune responses in macrophages ( 25 ) and the control of listeriosis in vivo ( 17 ). Previous studies have shown that CYLD limited RIPK2-mediated activation of NF-κB by removing K63-polyubiquitin chains from NEMO ( 8 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism through which ingested parasites may come into contact with NOD1 and NOD2, thereby triggering the synthesis of a variety of different cytokines, is poorly understood and still a matter of debate. On the basis of their cytosolic localization, NODs may respond to intracytosolic bacteria that have evaded from the phagosome, bacterial components delivered to the cytosol via the secretion systems or through created pores, and bacterial products delivered by phagocytosis or pinocytosis [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…31 The mutations have been shown to lead to significant hyperactivity of NOD1 and NOD2 receptors after ligand stimulation. 32 Therefore, we suggest that the NOD1 rs2075818 polymorphism may contribute to the pathogenesis of subacute sclerosing panencephalitis. There have been no studies yet on the NOD1 gene polymorphisms in subacute sclerosing panencephalitis.…”
Section: Discussionmentioning
confidence: 85%